2015
DOI: 10.1177/0269881115578159
|View full text |Cite
|
Sign up to set email alerts
|

Role of the serotonin transporter gene locus in the response to SSRI treatment of major depressive disorder in late life

Abstract: It has been suggested that the serotonin or 5-hydroxytriptamine (5-HT) transporter (5-HTT) and its gene-linked polymorphic region (5-HTTLPR) are selective serotonin reuptake inhibitor (SSRI) response modulators in late-life depression (LLD), and particularly in late-life major depressive disorder (MDD). Previous studies differed in design and results. Our study aimed to investigate the solute carrier family 6 (neurotransmitter transporter and serotonin) member 4 (SLC6A4) gene locus, encoding 5-HTT and SSRI tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 64 publications
0
6
0
3
Order By: Relevance
“…In 214 depressed white patients treated with various SSRIs, 5‐HTTLPR genotype was not significantly associated with overall ADR incidence or any specific ADR domain, although S allele carriers had numerically higher incidence in most domains . A study of 234 late‐life depression patients treated with SSRIs found no association between 5‐HTTLPR genotype and dropout due to ADRs . The largest study that failed to show an association between 5‐HTTLPR and ADRs or dropout rate was performed using a subset of depressed European ancestry patients treated with escitalopram in the Genome Based Therapeutic Drugs for Depression (GENDEP) project (n=450) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 214 depressed white patients treated with various SSRIs, 5‐HTTLPR genotype was not significantly associated with overall ADR incidence or any specific ADR domain, although S allele carriers had numerically higher incidence in most domains . A study of 234 late‐life depression patients treated with SSRIs found no association between 5‐HTTLPR genotype and dropout due to ADRs . The largest study that failed to show an association between 5‐HTTLPR and ADRs or dropout rate was performed using a subset of depressed European ancestry patients treated with escitalopram in the Genome Based Therapeutic Drugs for Depression (GENDEP) project (n=450) .…”
Section: Resultsmentioning
confidence: 99%
“…12 On the contrary, seven studies of white populations have found no association between 5-HTTLPR and tolerability. [13][14][15][16][17][18][19] One of the earliest publications examining broad SSRI tolerability by SLC6A4 genotypes demonstrated no difference in mean number of ADRs by 5-HTTLPR genotype in 36 depressed white patients treated with fluoxetine, although there were compelling associations between genotype and neuropsychiatric side effects that are covered elsewhere in this review. 13 In 74 pediatric patients treated with citalopram, there was no association between 5-HTTLPR genotype and risk of individual ADRs with the exception of agitation.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Genomic DNA was purified from fresh/frozen blood samples following salting-out method [41]. Analysis of the 5-HTTLPR and apolipoprotein E (APOE) polymorphisms were made in blinded fashion previously described [42, 43].…”
Section: Methodsmentioning
confidence: 99%
“…The results of genotyping in the 5-HTTLPR region in this retrospective study indicate that carriers of the short alleles, same in heterozygosity, exhibit better performance in financial activities and a lower percentage of economic losses compared to homozygotes for the long allele. The relationship of SLC6A4 5-HTTLPR polymorphism with variable serotonin expression has been associated with neuropsychiatric conditions [ 11 ], social anxiety disorder [ 31 ], aggressiveness [ 32 ], depression [ 33 ] and impulsivity [ 34 ], diseases that contribute to the deficit in the time perception. However, genetic studies associated with cognitive parameters are not only linked to SLC6A4 5-HTTLPR [ 35 ], but the studies by Burt and Mikolajewski [ 36 ] show that that subjects make less harmful decisions, besides an adjuvant action of variations in the 5HTR2A gene on cognitive aspects.…”
Section: Introductionmentioning
confidence: 99%